A new Cretaceous thyreophoran from Patagonia supports a South American lineage of armoured dinosaurs - Riguetti, Facundo Javier (2022)
The early evolution of thyreophoran dinosaurs is thought to have occurred primarily in northern continents since most evidence comes from the Lower and Middle Jurassic of Europe and North America. The diversification into stegosaurs and ankylosaurs is obscured by a patchy fossil record comprising only a handful of fragmentary fossils, most with uncertain phylogenetic affinities. Here we report the discovery of a new armoured dinosaur from the early Late Cretaceous of Argentina, recovered phylogenetically using various datasets either as a basal thyreophoran or a stem ankylosaur, closely related to Scelidosaurus. It bears unusual anatomical features showing that several traits traditionally associated with the heavy Cretaceous thyreophorans did not occur universally. Jakapil kaniukura gen. et sp. nov. is the first definitive thyreophoran species from the Argentinian Patagonia. Unlike most thyreophorans, it seems to show a bipedal stance, as in Scutellosaurus. Jakapil also shows that early thyreophorans had a much broader geographic distribution than previously thought. It is a member of an ancient basal thyreophoran lineage that survived until the Late Cretaceous in South America.